From Political to Economic Awakening in the Arab World : The Path of Economic Integration - Deauville Partnership Report on Trade and Foreign Direct Investment, Volume 1. Overview Report - World Bank (Washington, DC, 2012)
The forces unleashed by the Arab political awakening have the power to be transformational. One critical parameter of success will be whether the Arab political awakening is accompanied by a concurrent economic awakening. Economic integration through increased trade and foreign direct investment (FDI) is one key means available in the short to medium term to policy makers to put the Partnership countries on a higher path of sustainable economic growth and in a position to decisively tackle the problem of unemployment, especially youth unemployment. To be sure, skepticism abounds in the region over the merits of trade and FDI and the integrity of the private sector in light of "crony capitalism," where the benefits of past policies are perceived to have accrued only to a well-connected few. Leadership is needed in both Partnership countries and Deauville partners to provide a credible long-term vision and explain the mutual benefits of economic integration. One such powerful vision could be the pursuit of a partnership aimed at gradually promoting four key freedoms in the Mediterranean and beyond: the free movement of goods, services, capital, and eventually persons. The implementation of far-reaching domestic reforms in Partnership countries will be critical to effectively reap the growth and employment opportunities offered by greater economic integration and regulatory convergence with the most advanced economies. To further enhance trade and FDI and to achieve the vision of an Arab world more integrated into global markets, the trade and commerce pillar of the Deauville Partnership could therefore focus on four overarching priority areas of reforms and support: (a) improve market access opportunities and market regulations; (b) foster competitiveness, diversification, and employment; (c) facilitate trade and mobilize trade finance and diaspora resources; and (d) promote the inclusiveness, equity, and sustainability of the structural transformation brought about by the process of integration.